Bacteriophage-Derived Depolymerases against Bacterial Biofilm - Gracja Topka-Bielecka; Aleksandra Dydecka; Agnieszka Necel; Sylwia Bloch; Bożena Nejman-Faleńczyk; Grzegorz Węgrzyn; Alicja Węgrzyn (MDPI AG, 2021)
In addition to specific antibiotic resistance, the formation of bacterial biofilm causes another level of complications in attempts to eradicate pathogenic or harmful bacteria, including difficult penetration of drugs through biofilm structures to bacterial cells, impairment of immunological response of the host, and accumulation of various bioactive compounds (enzymes and others) affecting host physiology and changing local pH values, which further influence various biological functions. In this review article, we provide an overview on the formation of bacterial biofilm and its properties, and then we focus on the possible use of phage-derived depolymerases to combat bacterial cells included in this complex structure. On the basis of the literature review, we conclude that, although these bacteriophage-encoded enzymes may be effective in destroying specific compounds involved in the formation of biofilm, they are rarely sufficient to eradicate all bacterial cells. Nevertheless, a combined therapy, employing depolymerases together with antibiotics and/or other antibacterial agents or factors, may provide an effective approach to treat infections caused by bacteria able to form biofilms.